تطبيق وسائل الصور في تعليم المفردات لتنمية مهارة الكلام بكتاب رَأْسٌ سِيْرَاهْ لصف الثاني بالمدرسة الإبتدائية الحكومية كرطاريجا 2 عورا جومبانج: Media Gambar dalam Pembelajaran Mufrodat Kitab Ro’sun Sirah untuk Meningkatkan Maharah Kalam di SDN Kertorejo 2 Ngoro Jombang - Abidin, Hasan; Ni’mah, Ma’rifatul Kamiliatun (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2024)
The background to this research and development is that researchers found students' difficulties and lack of interest in learning Arabic vocabulary. Apart from that, there is a lack of other media that supports learning Arabic vocabulary, while the facilities at SDN Kertorejo 2 are quite adequate. So students need interesting media, in this case in the form of image media. The creation and development of this learning media was carried out to overcome the problems faced by students at SDN Kertorejo 2. The researcher chose a design from the Canva application and then designed it attractively so that it could be accepted and liked by students so as to increase their interest in learning Arabic, especially vocabulary to improve speaking skills. Arabic. Researchers use research methods with a research and development approach. Previous researchers conducted observations and interviews with students at SDN Kertorejo 2. After obtaining the necessary data, the researchers created learning media in accordance with the students' expectations and needs and still referred to the applicable curriculum. Then the researchers applied learning media to students at SDN Kertorejo 2 who, although they still experienced several problems and obstacles, these problems could still be overcome with other facilities and equipment available at the school. In the application of image media carried out on second grade students in elementary schools, it can be concluded that the use of image media in learning Arabic vocabulary in the book